Graded Exposure and Self-Instruction Group Counseling to Reduce Self Handicapping - Inta, Suhartono; Awalya, Awalya; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
The tendency of performing self-handicapping by students is somehow potential to reduce their academic achievement. Thus, this study strived for examining the effect of graded exposure and self-instruction group counseling to reduce students’ self-handicapping behavior in Kendari City, Southeast Sulawesi. Experimental method was carried out with pretest-posttest comparison group design involving 21 people divided into three groups chosen using purposive sampling from 150 students of Islamic Junior High School (MTs) in Kendari City, Southeast Sulawesi. Findings indicated that the two kinds of counseling could effectively reduce students’ tendency to do self-handicapping. In addition, the Mann Whitney test showed that the group counseling done using self-instruction was more effective than the graded exposure. Regarding these findings, counselors are recommended to implement self-instruction technique to reduce the self-handicapping behavior by Junior High School students.